ECOPRENEURSHIP ON PROJECT-BASED LEARNING (PBL) : AN APPROACH TO INCREASE LEARNING RESPONSE IN PHYSICS - NOER ABIDIN, ENDAH; HARIYONO, EKO (Inovasi Pendidikan Fisika, 2019)
This research aims to examine students? response to the implementation of ecopreneurship-oriented Project-Based Learing (PBL) model in physics learnig. The type of this reasearch is descriptive quantitative with true-experimental methods and control group pre-test and post-test design, which is applied to 49 science-majored sophomore students in SMA Negeri 1 Mojosari, Mojokerto.Students? response were collected through responses questionnaire which is arranged with Likert scale and the results were analyzed descriptive-quantitatively. Based on the results? analysis, students? response to ecopreneurship-oriented PBL model is in very good criteria with the average percentage of 83% which shows that the model is well accepted by the students and able to be applied more on physics learning and other subjects.